(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Soil is one of fundamental components of life. It supports life and human habitat. The human habitats have evolved with advancement in science and technology. Humans tend to increase their living standards by constructing large number of utilities and infrastructure to accommodate their growing needs. Civil engineering has reached its new heights consequently more challenges are posed. Due to urbanisation and industrialisation population of cities and towns is increasing. This has resulted in growing networks of roads, rails and public places. Residential and commercial infrastructures are also on demand. Interesting thing to mention here is that all these activities are only possible if the underlying strata of crust called soil is able to withstand all these changes. Therefore the nature of soil on which a foundation or pavement is constructed determines the strength and durability of these structure. Interestingly some waste materials like Fly Ash with suitable activators may be use to make weak and expansive soils stable. By adding these materials the chemical as well as physical properties of the poor expansive soil can be suitably adjusted. In this research work the use of sodium based alkaline activators and fly ash as an additive in improving the geotechnical characteristics of expansive soils is worked out. Sodium hydroxide solutions 10, 12.5 and 15 molal with 1 Molar solution of sodium silicate were used as an activators. In this mix the activator to ash ratio was kept between 1 and 2.5, and ash percentages of 20, 30 and 40%, relatively to the total solids. Then it is tested by conducting the Unconfined compressive strength UCS at curing peri ods of 3,7 and 28 days respectively and then it is compared with that of a common fly ash based binder.